PTSD in prison settings: A systematic review and meta-analysis of comorbid mental disorders and problematic behaviours - Facer-Irwin, Emma; Blackwood, Nigel J.; Bird, Annie; Dickson, Hannah; McGlade, Daniel; Alves-Costa, Filipa; MacManus, Deirdre (PloS one, 2019)
Prevalence rates of PTSD are higher in the prison population than in the community. We sought to systematically review the extent to which this disorder is associated with other mental health disorders and problematic suicidal or aggressive behaviours in the prison population. Studies reporting a relationship between PTSD and comorbid mental disorders and/or problematic behaviours in imprisoned adolescent and adult populations were identified from four bibliographic indexes. Primary studies involving clinical interviews, validated instruments leading to DSM or ICD diagnoses, or validated self-report questionnaires such as the PTSD checklist were included. Random-effects meta-analysis was conducted where possible. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. This review identified 36 studies, with a combined sample of 9594 participants, (6478 male and 2847 female prisoners) from 11 countries. Thirty-four of the identified studies employed a cross-sectional design. We identified significant associations between PTSD and comorbid mental disorders including depression (OR = 3.4, 95% confidence interval (CI): 2.3-4.9), anxiety (OR = 2.9, 95% confidence interval (CI): 1.8-4.7) and substance use (OR = 1.9, 95% confidence interval (CI): 1.5-2.4). We also identified significant associations between PTSD and suicidality (OR = 3, 95% confidence interval (CI): 2.4-3.8) and aggressive behaviours (this latter finding was not subject to meta-analysis). Significant methodological heterogeneity was identified between studies. High rates of psychiatric comorbidity among prisoners with PTSD, and links to suicidal behaviour, self-harm and aggressive behaviour, provide further support for the need for trauma-informed treatment approaches in prisons. However, significant gaps in the current evidence were apparent. In particular, a lack of large, longitudinal studies meant that the temporal relationships between PTSD and relevant outcomes cannot currently be determined.